Effect of Acid Concentration on the Properties of Microcrystalline Cellulose from Pineapple Crown Leaf - Fitriani, Fitriani; Aprilia, Sri; Arahman, Nasrul; Bilad, Muhammad Roil (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
Microcrystalline cellulose was first extracted from pineapple crown leaf waste which is used very rarely as an alternative material from agricultural residue and then characterized. Microcrystalline cellulose was extracted from this waste through acid hydrolysis with various concentrations. The effect of acidconcentrations with sulfuric acid (H2SO4) on microcrystalline cellulose properties was investigated to determine its potential application as a material. Pineapple crown leaf was hydrolyzed for 2 hours at 45 along with various sulfuric acid concentrations (1, 2, and 3 M). The properties of the cellulose were evaluated by Scanning electron microscopy (SEM), Fourier transforms infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and thermogravimetric analysis (TGA). Among all the hydrolysis conditions carried out, the best hydrolysis condition was 3 M sulfuric acid. At this hydrolysis condition, the microcrystalline cellulose presented a rod-like shape, high crystallinity at 83.16%, and have average crystal size of 17.99 nm. The functional group and morphology analysis showed that the resulted product is maintained cellulose I structure and removal of non-cellulosic constituents and the chemical compositions. As for the thermal analysis, the temperature decreased from 177 (2 M sulfuric acid) to 149 (3 M sulfuric acid) because of the incorporation of sulfate groups after the hydrolysis process. Therefore, microcrystalline cellulose obtained from pineapple crown leaf waste has great potential as reinforcement in the manufacture of composites.